ANALISIS PENGARUH SUKU BUNGA, INFLASI, DAN NILAI TUKAR RUPIAH TERHADAP PROFITABILITAS BANK UMUM SWASTA NASIONAL DI BURSA EFEK INDONESIA - Setyaningsih Sri Utami, Cornelia Aryani Setyaningsih, Untung Sriwidodo & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to: 1) analyze the significance of the effect of interest rate on profitability 2) to analyze the significance of the effect of inflation rate on profitability 3) to analyze the significance of the effect of rupiah exchange rate on profitability 4) to analyze the significance of interest rate, inflation rate and exchange rate rupiah simultaneously to profitability. This research used survey method, data analysis technique using multiple linear regression analysis by using sampling technique with purposive sampling method. Hypothesistesting using t test (partial test), Test F (Simultaneous Test), and coefficient of determination (R2). The result of this research indicates that the interest rate of 0,318 and the inflation rate of 0,452 > 0,05 so no significant effect on profitability,while the Rupiah Exchange Rate of 0,018 < 0,05 affects profitability. Simultaneouslysignificance Interest Rate, Inflation Rate and Rupiah Exchange Rate affect the profitability of national private commercial banks in BEI period 2012 – 2016.Keywords: interest rate, inflation rate, rupiah exchange rate, profitability